2012
DOI: 10.3390/nu4111759
|View full text |Cite
|
Sign up to set email alerts
|

Does a Low Glycaemic Index (GI) Diet Cost More during Pregnancy?

Abstract: The aim of this study was to examine the monetary cost of dietary change among pregnant women before and after receiving low glycaemic index (GI) dietary advice. The pregnant women in this study were a subgroup of participants in the Pregnancy and Glycaemic Index Outcomes (PREGGIO) study. Twenty women from the low GI dietary advice group, who had completed their pregnancies, were randomly chosen. All these women had completed three day food records at 12–16 weeks and again around 36 weeks of gestation. Consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Previous support for a positive association of diet quality and cost has come from cross-sectional research, much of which assesses energy cost rather than daily diet cost, and for which the overall effect attributable to diet quality is small 20 . Only a small body of intervention research has examined the effect on cost of changes in diet quality 3235 ; these studies and the current analysis all find no increase in diet cost in association with improved diet quality. Additionally, we observed an inverse association of change in diet cost with change in WPFD among parents.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Previous support for a positive association of diet quality and cost has come from cross-sectional research, much of which assesses energy cost rather than daily diet cost, and for which the overall effect attributable to diet quality is small 20 . Only a small body of intervention research has examined the effect on cost of changes in diet quality 3235 ; these studies and the current analysis all find no increase in diet cost in association with improved diet quality. Additionally, we observed an inverse association of change in diet cost with change in WPFD among parents.…”
Section: Discussionmentioning
confidence: 49%
“…Diet cost was estimated using methods consistent with previous research 3235 . Price information from two online national supermarkets common to the study location was recorded and averaged for each food component reported (approximately 1600 items), except that prices for items reported from a named store or restaurant were obtained from these retail outlets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The weight of the literature suggests that consumers who spend more on food tend to have healthier diets as meaured by the Healthy Eating Index [22,23]. On the other hand, individuals who switch to a healthier diet-such as pregnant women following a low-glycemic diet [24] or obese children undergoing dietary treatment [25]-can do so without increasing their daily dietary costs.…”
Section: Diet Quality Income and Spendingmentioning
confidence: 99%